Analisis perencanaan keuangan daerah terhadap efektivitas anggaran daerah di Kota Lhokseumawe - Maulida, Raihan; Zulkarnain, Teuku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The study to analyze relationship between regional financial planning and regional budget effectiveness in supporting optimization of the Lhokseumawe city revenue and expenditure budget. Local financial planning is crucial element to ensure that budget allocations on target and accordance with regional development priorities. Regional budget effectiveness is measured through achievement of local revenue targets, expenditure efficiency, and budget alignment with regional medium-term development plan. The research method uses descriptive quantitative with secondary information analysis in form budget realization reports and regional financial planning documents fiscal 2018-2022. Effectiveness and efficiency ratio analysis is used to evaluate how well the budget used and whether financial targets and regional programs achieved. The results show that quality financial planning contributes significantly to budget effectiveness, especially when the planning process involves coordination across regional apparatus organizations and based on information on the actual needs of the community. The conclusion of study shows that careful and measurable financial planning improves effectiveness of local budget utilization.